Temporal validation of a simplified blastocyst grading system. (3rd April 2017) - Richardson, Alison; Brearley, Sophie; Ahitan, Saran; Chamberlain, Sarah; Davey, Tracey; Zujovic, Lyndsey; Hopkisson, James; Campbell, Bruce; Raine-Fenning, Nick
Abstract: We have recently established the clinical effectiveness and credibility of a simplified blastocyst grading system by demonstrating its prognostic potential and the inter- and intra-observer variability associated with it. To be considered clinically useful, however, the grading system also needs to be accurate (i.e. well calibrated with good discriminative ability). This study prospectively evaluates the performance of the grading system on subsequent patients from the same IVF unit in an attempt to temporally validate the model. All day 5 single embryo transfers between 1st July 2012 and 30th June 2014 were included in the study. The observed implantation, clinical pregnancy and live birth rates according to grade of embryo transferred were compared to the expected rates as predicted by the development data set and the statistical significance of any differences between the two were calculated using the Chi-square test. A total of 435 single embryo transfers were included. For each grade of embryo transferred, there was generally no significant difference between the observed and expected frequencies of implantation, clinical pregnancy and live birth suggesting that the simplified blastocyst grading system is accurate and temporal validation has been satisfactorily demonstrated. It is now necessary to externally validate the grading system to prove generality before further dissemination.